Automatic sub-word unit discovery and pronunciation lexicon induction for automatic speech recognition with application to under-resourced languages - Agenbag, Wiehan (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.